Energy‐efficient dynamic power allocation in multi‐antenna transmissions with imperfect channel estimation and feedback. Issue 21 (1st October 2015) - Yang, Ruizhe; Zheng, Chen; Wang, Zhuwei; Zhang, Yanhua; Yu, Fei Richard
Abstract : A dynamic power allocation scheme is proposed to maximise the energy efficiency (EE) for multi‐antenna transmissions when both the imperfect channel estimation and feedback are considered. The lower bounded ergodic EE is given by the temporal correlation analysis from the Kalman estimation and the differential codebook‐based feedback of the Gauss–Markov channel, based on which both the powers of data and training are adaptively optimised. Simulations show that the proposed dynamic power allocation scheme outperforms the traditional power allocation schemes.